Daytime sleepiness and specific food cravings: The moderating role of insulin sensitivity - Emma K. Romaker; Mason J. Krueger; Mollie S. Goldfinger; Alex Gonzalez; Daniel E. Forster; William K. Wohlgemuth; Roger C. McIntosh; Barry E. Hurwitz (PLoS ONE, 2026)
Purpose Daytime sleepiness is posited to stimulate hunger and food intake of specific macronutrients such that obesity and type 2 diabetes mellitus risk may be elevated. To assess this hypothesis, this study of insulin sensitive and insulin resistant non‑diabetic individuals utilized standardized meal administration conditions to examine: 1) the extent to which self-reported sleepiness was associated with specific food cravings over the course of a day; and 2) whether insulin sensitivity interactively influenced this relationship. Methods Non-diabetic men and women (N = 143) participated in one session, where a euglycemic-hyperinsulinemia clamp was used to provide an insulin sensitivity index, and in a subsequent 14‑hour session, where four standardized mixed-meals and one pre-bedtime meal were provided. Concurrent pre-meal measures of sleepiness and cravings for sweet, salty, and starchy foods, and fruit, meat, and dairy foods were obtained. Hierarchical linear modeling analyses examined the within- and between-person association of sleepiness with food cravings across meals as a function of insulin sensitivity, controlling for age, sex and caloric intake administration. Results Craving ratings were highest for fruits, followed by dairy and starchy foods, meat, and then salty and sweet foods (p < .001). Analyses showed that insulin sensitivity moderated the positive association of daytime sleepiness with all food cravings, except for salty foods (p = .011 to .036), independent of covariates. This moderation effect displayed the strongest magnitude at below-average and average insulin sensitivity levels (p < .001). Conclusions Study results extend previous findings to show that daytime sleepiness is positively associated with cravings for a range of food types. The fact that these associations were increased in persons with more diminished insulin sensitivity is novel and supports further examination of underlying mechanisms linking daytime sleepiness and food cravings with food consumption and metabolic dysregulation early in diabetes pathophysiology.